2019
DOI: 10.3847/1538-3881/ab4d4a
|View full text |Cite
|
Sign up to set email alerts
|

IRAS 09002-4732: A Laboratory for the Formation of Rich Stellar Clusters

Abstract: IRAS 09002-4732 is a poorly studied embedded cluster of stars in the Vela Molecular Ridge at a distance of 1.7 kpc. Deep observations with the Chandra X-ray Observatory, combined with existing optical and infrared surveys, produce a catalog of 441 probable pre-main sequence members of the region. The stellar spatial distribution has two components: most stars reside in a rich, compact, elliptical cluster, but a minority reside within a molecular filament several parsecs long that straddles the cluster. The fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
2
5
0
Order By: Relevance
“…The 90 𝜇m dust emission map in Figure 14 shows a matched structure with ASKAP toward the H region but little H𝛼 emission. This suggests the region is dominated by cold dense gas, which is consistent with the analysis done by Getman et al (2019) that the H region is young. The "*" on the images marks the location of the H region as listed in the WISE Catalogue.…”
Section: Gal 2684-009 H Regionsupporting
confidence: 89%
See 2 more Smart Citations
“…The 90 𝜇m dust emission map in Figure 14 shows a matched structure with ASKAP toward the H region but little H𝛼 emission. This suggests the region is dominated by cold dense gas, which is consistent with the analysis done by Getman et al (2019) that the H region is young. The "*" on the images marks the location of the H region as listed in the WISE Catalogue.…”
Section: Gal 2684-009 H Regionsupporting
confidence: 89%
“…The H region GAL 228.4-00.9 (also known as IRAS 09002-4732) is located at RA 09:01:54.3, Dec -47:43:59 (J2000). The parallax measurements from ESA's Gaia satellite suggests a distance of 1.7-1.8 kpc for the cluster (Getman et al 2019) which places it along the edge of the Vela Molecular cloud, inline with RCW 38. Getman et al (2019) completed a survey of the little-known region using x-ray and infrared data.…”
Section: Gal 2684-009 H Regionmentioning
confidence: 95%
See 1 more Smart Citation
“…The work by Tobin et al (2009) have shown the similarity in the kinematics between the stars and 13 CO gas in the ISF. Subsequently, Hacar et al (2016); Stutz & Gould (2016); Getman et al (2019) explored the kinematic link between YSOs and the cloud gas in Orion A. Together with our findings, these results suggest that SF is ongoing in the ISF and that the low velocity dispersion in the protostars relative to their local gas probably originates from the low core-to-envelope velocity reported here.…”
Section: The Dynamical Status Of the Isfsupporting
confidence: 79%
“…Recent analyses with APOGEE and Gaia surveys have shown that the ONC is slowly expanding (Kounkel et al 2018;Kuhn et al 2019), raising the question that whether gas is falling into ONC. However, it is possible if the ISF collapsing direction is toward OMC-1 (the densest gas region in the ISF), as Getman et al (2019) recently have suggested that the stars in the OMC-1 region are undergoing gravitational contraction. On the other hand, Getman et al (2019) showed that OMC-4/5 are not moving toward OMC-1.…”
Section: The Dynamical Status Of the Isfmentioning
confidence: 99%